2006
DOI: 10.1097/01.mpg.0000214163.83316.41
|View full text |Cite
|
Sign up to set email alerts
|

Amylase‐Resistant Starch as Adjunct to Oral Rehydration Therapy in Children with Diarrhea

Abstract: In children with acute diarrhea, the addition of amylase-resistant starch to glucose ORS significantly shortened duration of diarrhea compared with standard treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 19 publications
1
37
1
2
Order By: Relevance
“…On the other hand, more recent studies in adults with cholera-like diarrhea episodes, it was found that substituting resistant starch for glucose in hypo-osmolar oral rehydration solution significantly improves response to ORS (RAMAKRISHNA et al, 2008). Similar results were reported in children with acute diarrhea (RAGHUPATHY et al, 2006). In both cases, the addition of resistant starch to glucose ORS significantly shortened duration of diarrhea compared with standard treatment.…”
Section: Time-course Of Diarrhea Episodessupporting
confidence: 73%
“…On the other hand, more recent studies in adults with cholera-like diarrhea episodes, it was found that substituting resistant starch for glucose in hypo-osmolar oral rehydration solution significantly improves response to ORS (RAMAKRISHNA et al, 2008). Similar results were reported in children with acute diarrhea (RAGHUPATHY et al, 2006). In both cases, the addition of resistant starch to glucose ORS significantly shortened duration of diarrhea compared with standard treatment.…”
Section: Time-course Of Diarrhea Episodessupporting
confidence: 73%
“…They are not in the normal diet, but they are synthesized by colonic bacteria from nonabsorbed carbohydrate. Thus, the addition of resistant starch (RS; starch that is relatively resistant to amylase digestion) to ORS should result in increased production of SCFAs and has been shown to enhance the effectiveness of ORS in the treatment of both cholera in adults and noncholera diarrhea in children (149,150). Subsequent studies established that RS in HO-ORS substantially decreases both stool output and the time to the first formed stool in adults with cholera (151).…”
Section: Scientific Challenges That Remainmentioning
confidence: 99%
“…Initially, glucose was the first carbohydrate to be used (Desjeux et al, 1994). Then, rice (Molla et al, 1982;Gore et al, 1992;Desjeux et al, 1994;Dutta et al, 2000) and more recently amylase-resistant starch (ARS) (Ramakrishna et al, 2000Raghupathy et al, 2006) added to glucose ORS has proven to be more effective than glucose ORS without ARS.…”
Section: Introductionmentioning
confidence: 99%